Utilization of a Green Brominating Agent for the Spectrophotometric Determination of Pipazethate HCl in Pure Form and Pharmaceutical Preparations - Ayman A. Gouda (Journal of Spectroscopy)
Five simple, accurate, and sensitive spectrophotometric methods (A–E) have been described for the indirect assay of pipazethate HCl (PZT) either in pure form or in pharmaceutical preparations. The proposed methods are based on the bromination of pipazethate HCl with a solution of excess bromate-bromide mixture in hydrochloric acid medium and subsequent estimation of the residual bromine by different reaction schemes. In the first three methods (A–C), the determination of the residual bromine is based on its ability to bleach the color of methyl orange, indigo carmine, or thymol blue dyes and measuring the absorbance at 520, 610, and 550 nm for methods A, B, and C, respectively. Methods D and E involves treating the unreacted bromine with a measured excess of iron(II), and the remaining iron(II) is complexed with 1,10-phenanthroline, and the increase in absorbance is measured at 510 nm for method D and the resulting iron(III) is complexed with thiocyanate and the absorbance is measured at 480 nm for method E. The different experimental parameters affecting the development and stability of the color are carefully studied and optimized. Regression analysis of the Beer-Lambert plots showed good correlation in the concentration ranges of 0.5–8.0 μg . The apparent molar absorptivity, Sandell's sensitivity, detection and quantitation limits were evaluated. The proposed methods have been applied and validated successfully for the analysis of the drug in its pure form and pharmaceutical formulations with mean recoveries of 99.94%–100.15% and relative standard deviation ≤1.53. No interference was observed from a common pharmaceutical adjuvant. Statistical comparison of the results with the reference method shows excellent agreement and indicates no significant difference in accuracy and precision.